A multi-functional nano-system combining PI3K-110α/β inhibitor overcomes P-glycoprotein mediated MDR and improves anti-cancer efficiency. (1st June 2023) - Lin, Ruikun; Zhang, Lei; Ye, Biwei; Wang, Yanan; Li, Yi-Dong; Jason, Hsu; Liu, Wenzhen; Hu, Ping; Chen, Jincan; Chen, Zhe-Sheng; Chen, Zhuo
Abstract: P-glycoprotein (P-gp/ABCB1)-mediated multidrug resistance (MDR) in cancers severely limit chemotherapeutic efficacy. We recently reported that phosphatidylinositol-3-kinase (PI3K) 110α and 110β subunits can be novel targets for reversal of P-gp mediated MDR in cancers, and BAY-1082439 as an inhibitor specific for PI3K 110α and 110β subunits could reverse P-gp-mediated MDR by downregulating P-gp expression in cancer cells. However, BAY-1082439 has very low solubility, short half-life and high in-vivo clearance rate. Till now, nano-system with the functions to target PI3K P110α and P110β and reverse P-gp mediated MDR in cancers has not been reported. In our study, a tumor targeting drug delivery nano-system PBDF was established, which comprised doxorubicin (DOX) and BAY-1082439 respectively encapsulated by biodegradable PLGA-SH nanoparticles (NPs) that were grafted to gold nanorods (Au NRs) modified with FA-PEG-SH, to enhance the efficacy to reverse P-gp mediated MDR and to target tumor cells, further, to enhance the efficiency to inhibit MDR tumors overexpressing P-gp. In-vitro experiments indicated that PBDF NPs greatly enhanced uptake of DOX, improved the activity to reverse MDR, inhibited the cell proliferation, and induced S-phase arrest and apoptosis in KB-C2 cells, as compared with free DOX combining free BAY-1082439. In-vivo experiments further demonstrated that PBDF NPs improved the anti-tumor ability of DOX and inhibited development of KB-C2 tumors. Notably, the metastasis of KB-C2 cells in livers and lungs of nude mice were inhibited by treatment with PBDF NPs, which showed no obvious in-vitro or in-vivo toxicity. Highlights: MDR limit chemotherapy against cancers, and nano-systems that can target P110α or P110β and inhibit MDR were not reported. BAY-1082439 can inhibit P110 subunits, attenuate P-gp-mediated MDR in cancers but is poorly soluble and unstable in blood. ·Here we constructed a multi-functional drug-loading nano-system PBDF for inhibiting the MDR KB cells overexpressing P-gp. BAY1082439@PLGA-SH, DOX@PLGA-SH NPs, and SH-PEG-FA were grafted to gold nanorods and PBDF was established. PBDF NPs inhibited proliferation of MDR KB-C2 cancer cells and KB-C2 tumor growth, and reduced metastasis of KB-C2 cells.